Intergovernmental relations in transition reflections and directions - Hamilton, David K.; Stenberg, Carl W. (Routledge, Taylor & Francis Group, 2018)
"The field of intergovernmental relations has changed substantially in the past two decades, and it holds a critical and evolving role in the US federal system as well as in public policy and management. Building upon the legacy of Deil S. Wright's scholarship, this collection of essays by distinguished scholars, emerging thought leaders, and experienced practitioners chronicles and analyzes some of the tensions and pressures that have contributed to the current state of intergovernmental relations. Although rarely commanding media attention by name, intergovernmental relations are being elevated in the public discourse through policy issues dominating headlines and addressed in this book, including health insurance exchanges under the now-threatened Affordable Care Act, the roles of the federal, state, and local governments in K-12 education, recent controversies over campus sexual assaults, state legalization of medical and recreational marijuana use, and civil unrest over police killings of African-Americans bringing renewed calls for federal civil-rights intervention and criticisms of the federal government's role in militarizing local police. Contributors emphasize interpretation and assessment of the impacts of these issues on the future directions of the intergovernmental relations field. This book will serve as an ideal textbook for courses on intergovernmental relations and federalism, and will be of use to practitioners, nonprofit organizations involved in public policy and management, and civic organizations who are players in intergovernmental management"-- Provided by publisher.